The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1365-3156.1999.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

The performance of school‐based questionnaires of reported blood in urine in diagnosing Schistosoma haematobium infection: patterns by age and sex

Abstract: SummaryThis study investigates the performance of school-based questionnaires of reported blood in urine as an indicator of the prevalence of Schistosoma haematobium infection in schools and the presence of infection in individuals. In most schools (87%), the prevalence of reported blood in urine underestimates the prevalence of S. haematobium infection. Predictive value analysis suggests that a threshold of 30% reported blood in urine would identify most of the high prevalence schools (i.e. those with 50% or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 7 publications
5
36
0
Order By: Relevance
“…However, in older girls, considerable differences were found between the questionnaire responses and the field survey data. These patterns are consistent with previous reports (Guyatt et al 1999) and were also strikingly consistent across distinct geographical areas of Tanzania, incorporating coastal and inland regions (Figure 1). The Bayesian models demonstrated that age-gender effects were consistent across all geographical regions of Tanzania.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in older girls, considerable differences were found between the questionnaire responses and the field survey data. These patterns are consistent with previous reports (Guyatt et al 1999) and were also strikingly consistent across distinct geographical areas of Tanzania, incorporating coastal and inland regions (Figure 1). The Bayesian models demonstrated that age-gender effects were consistent across all geographical regions of Tanzania.…”
Section: Discussionsupporting
confidence: 92%
“…For example, older school-aged girls (i.e. >13 years) were more likely to under-report the occurrence of urinary schistosomiasis using morbidity questionnaires (Guyatt et al 1999;Ansell et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies carried out in Tanzania observed that girls were more likely than boys to be missed in self-diagnosis screening for S. haematobium [10,11]. These studies confirmed previous reports of under-reporting of haematuria and schistosomiasis by girls at school level.…”
Section: Discussionsupporting
confidence: 82%
“…The chronic infections have been associated with hepatomegaly, splenomegaly, periportal fi brosis, urinary bladder obstructions, and bladder cancer. [16][17][18] Although being diffi cult to accurately quantify, parasitic infection has been shown to be a causal factor for hepatomegaly and splenomegaly in the region. These morbidities have shown a strong relationship.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Use of portable ultrasound improves accessibility and removes some of the constraints of upkeep. Studies [15][16][17][18][19][20] have shown that the introduction of ultrasound can significantly alter treatment plan. In 43% of cases in Rwanda, ultrasound changed the initial management plan, involving surgical procedure, medication, clinic referral and others.…”
Section: Discussionmentioning
confidence: 99%